Adolescents Develop Their Identities Amidst Adversities - Idrus, Faizah; Nik Abdul Rahman, Nik Suryani; Hussein, Suhailah; Rais, Haniza (Advances in Social Sciences Research Journal, 2021)
Adolescence is a somewhat turbulent phase of life to many. This paper explores the challenges of 6 Malaysian adolescents aged between 13 and 17 from low socioeconomic background in developing their identities. In depth semi-structured interviews were carried out. Family problems, peer pressure, and learning difficulties were among the main issues encountered. This study revealed that although the respondents’ families’ socio-economic status had affected them, it is not the determinant to their success nor failure. This study also suggests that a sound identity development and academic outcome could be achieved with relatively good parental involvement, well perceived expectations, fitting in with group of friends as well as a healthy surrounding